Getting Away With Murder: Homicide Clearance by Arrest in Chicago and Its Community Areas - Ferrandino, Joseph (Homicide studies, 2021)
This work explores the decline in murder clearances through arrest in Chicago from 1965 through 2015, specifically focusing on the most recent time period since 2001. The findings suggest that clearance by arrest has decreased significantly, that elapsed time is a limited factor in clearing more murders through arrest and that factors associated with clearance by arrest in Chicago have changed over time. These results lead to a discussion on the missing variance that cannot explain murder clearance by arrest as well as future research areas that can explore why many murderers in Chicago are increasingly escaping the justice system.